Deformation mechanism of twinning-detwinning of wrought and constrained groove pressing processed magnesium AZ31B alloy - Zhang, H (2018)
Magnesium alloys have attracted great interest in the 21st century as ultra lightweight metallic structural materials with outstanding mechanical properties. AZ31B alloy is one of the most widely used magnesium wrought alloys in sheet form for which twinning, a dominant plastic deformation mechanism at room temperature, remains less well understood than crystal slip. The main objective of this thesis is to advance, both experimentally and numerically, the understanding of the mechanism and the conditions of the twinning-detwinning (TDT) process, and the influence of these processes on the mechanical deformation response of magnesium AZ31B alloy in the wrought and constrained groove pressing (CGP) processed conditions. To achieve this goal in the present study, new applications of Digital Image Correlation (DIC) analysis were developed for two strain evaluation techniques. In the context of the Focused Ion Beam (FIB)-DIC micro-ring-core method of residual stress evaluation, platinum deposition at the sample surface in the Scanning Electron Microscope vacuum chamber led to a dramatic improvement of the correlation accuracy. Another new approach was proposed to track the strain-induced changes in the Debye-Scherrer rings on 2D powder X-ray diffraction (XRD) patterns using DIC (referred to as XRD-DIC) allowing to minimise the error and increase the efficiency of obtaining the full in-plane strain information. The effect of twinning on the deformation asymmetry was studied by ex situ XRD on a bent bar of wrought sample. The asymmetry of twinning was shown to lead to the variation in the plastic strain accommodation efficiency, which affected yielding. Furthermore, wrought and/or CGP processed samples were examined under in situ cyclic loading by XRD and electron backscatter diffraction for comparison. The first cycle exhibited a clear difference in the twin volume fraction and activation of TDT compared to the subsequent cycles. An advanced crystal plasticity finite element model of crystal slip, twinning and detwinning was developed to simulate the behaviour of a wrought sample subjected to compression-tension loading. Information on the activity of deformation systems and the critical resolved shear stress for detwinning was obtained. The model gave new insights into the non-Schmid behaviour (grain neighbour effects) for twinning, and particularly for detwinning. The grain neighbour effect becomes more pronounced with increasing plastic strain level, particularly when detwinning dominates the deformation response.